2009
DOI: 10.1021/jp809990a
|View full text |Cite
|
Sign up to set email alerts
|

Single-Sized CdSe Nanocrystals with Bandgap Photoemission via a Noninjection One-Pot Approach

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
138
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(149 citation statements)
references
References 58 publications
10
138
1
Order By: Relevance
“…Unlike gel permeation chromatography (GPC), PFG NMR is less dependent on the choice of solvent and has stimulated NMR researchers to explore the applicability of NMR to probe MWD of various polymeric systems. [ 4,5 ] Rather frequently, we have noticed that the pulsed gradient stimulated echo (PGSTE) NMR response of various…”
Section: Introductionmentioning
confidence: 99%
“…Unlike gel permeation chromatography (GPC), PFG NMR is less dependent on the choice of solvent and has stimulated NMR researchers to explore the applicability of NMR to probe MWD of various polymeric systems. [ 4,5 ] Rather frequently, we have noticed that the pulsed gradient stimulated echo (PGSTE) NMR response of various…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most important II-VI nanocrystals, cadmium selenide (CdSe) becomes a 'model' nanocrystal system for a hotspot of basic studies on the photoelectrical properties of nanocrystals because of its accessibility of high-quality and stability [11]. Recently, the family of colloidal CdSe with a narrow-sized distribution, which is similar to regular nanocrystals, has attracted much attention of the researchers [12][13][14][15][16][17][18][19][20][21]. The CdSe nanocrystals with the narrow-sized distribution hold great promising for the various applications based on a rational design supported by the understanding of nucleation and growth [16].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al prepared multiple families of CdSe with a narrow bandgap via non-injection one-pot syntheses, showing sharp absorption and emission peaks [19]. Results demonstrated that low acid-to-Cd and high Cd-to-Se feed molar ration are critical for preparing the narrow-sized CdSe [20]. In addition, they proposed a thermodynamic equilibrium driven approach for the formation of CdSe nanocrystals, which featured highly synthetic reproducibility [21].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike GPC, PGSE NMR is less dependent on the choice of solvent and has stimulated NMR researchers to explore the applicability of NMR to probe MWD of various polymeric systems. [4,5] A particular challenge is related to the data processing of the PGSE NMR decay curves to obtain reliable relations between the distribution of diffusivity and the MWD, e.g., bi-exponential fitting, [6] sum of one-parameter functions (e.g., convoluted exponentials, as well as pure exponentials) using a program denoted SPLMOD, [7] component resolved (CORE) [8] and direct exponential curve resolution algorithm (DECRA). [9] When dealing with complex samples showing severe peak overlap with small differences in derived diffusion coefficients, one may apply multivariate curve resolution (MCR), MCR alternating least square (MCR-ALS) analysis, [10] MCR with non-linear least square regression (MCR-NLR) [11] and Maximum entropy (MaxEnt) processing techniques.…”
Section: Introductionmentioning
confidence: 99%